DIGITAL HEALTH SOLUTIONS FOR SCREENING AND ONGOING SURVEILLANCE OF CHRONIC NON-COMMUNICABLE DISEASE PATIENTS - Khodjieva Gulirano Sayfullaevna (Modern American Journals, 2025)
This study evaluates the effectiveness of digital health technologies in early detection and ongoing monitoring of patients with chronic non-communicable diseases (NCDs) such as diabetes, cardiovascular pathologies, and bronchial asthma. The aim is to assess how digital tools improve self-control, clinical outcomes, and patient satisfaction.
Keywords: information technologies, chronic diseases, screening, dynamic monitoring, digital health, telemedicine, medical applications.